Distally Based Peroneus Brevis Muscle Flap for Large Leg, Ankle, and Foot Defects: Anatomical Finding and Clinical Application - Abd-Al-Moktader, Magdy Ahmed (Journal of Reconstructive Microsurgery, 2018)
Background Peroneus brevis muscle flap is a distinguished, distally based safe flap that can be manipulated to cover small defects in the leg and ankle. For large-sized defects, a more distal, larger flap is required either locally or distantly.Methods Forty-two distally based peroneus brevis muscle flaps were elevated in 42 patients (30 males and 12 females) with major lower leg, ankle, and proximal foot defects of 6 to 15 cm in length and 6 to 12 cm in width. Anatomical findings were recorded as number, size, and sources of blood supply, entry sites, the lowermost two arterial supplies, internal distribution of blood supply to the muscle, the relationship between external and internal distribution of the blood vessels, the length of the muscle, the entry site of the main artery, and the splitting of the proximal portion of the peroneus brevis muscle to increase its width to sufficiently cover large defects.Results The anatomical findings suggested that the muscle can be safely extended to cover a large defect in the leg, ankle, or proximal foot. In addition, the longitudinal splitting of the muscle increases its width by up to three times, making it an excellent long-surviving flap to cover a large defect.Conclusion A distally based peroneus brevis muscle flap has a rich blood supply and safely reaches the proximal foot, with a secure splitting to cover large defects in the leg, ankle, and proximal foot.
Keywords: distally based peroneus brevis muscle flap; muscle flap in leg, ankle and foot defects; leg, ankle and foot coverage